2018
DOI: 10.6002/ect.2017.0096
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: There is a clear lack of clinical evidence guiding immunosuppressive management in longterm stable liver transplant recipients. As a result, anecdotal experience suggests wide variability across transplant centers. We aimed to identify patterns of immunosuppression practices in liver transplant centers across Canada and the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This survey suggests that transplantation centers are worried about graft rejection, perhaps in the light of the previous weaning studies and thus do not perform immunosuppression discontinuation. 61 In our routine practice, each patient receives an individualized combination therapy, which may be minimized without being totally discontinued. Intravenous methylprednisolone is administered from postoperative day 1-5 in tapering doses and then 30 mg per oral (PO) is administered by postoperative day 6.…”
Section: Long -Term Immunosuppressionmentioning
confidence: 99%
“…This survey suggests that transplantation centers are worried about graft rejection, perhaps in the light of the previous weaning studies and thus do not perform immunosuppression discontinuation. 61 In our routine practice, each patient receives an individualized combination therapy, which may be minimized without being totally discontinued. Intravenous methylprednisolone is administered from postoperative day 1-5 in tapering doses and then 30 mg per oral (PO) is administered by postoperative day 6.…”
Section: Long -Term Immunosuppressionmentioning
confidence: 99%
“…The combination of drugs seems to be important however with the effects of tacrolimus on MSC being reversed by the combined use of oxytocin (118). Whilst it has been demonstrated that avoidance of corticosteroids in patients following a liver transplantation is likely to be safe and reduce associated complications (119), corticosteroids are still widely used in the setting of liver transplantation, both for induction of immunosuppression and treatment of rejection (120). When combined with dexamethasone in in vitro assays the ability of MSC to suppress T cell proliferations seems to be reversed (121), however the ability of MSC to suppress natural killer cell activation seems to be enhanced with dexamethasone augmenting the ability of MSC to IL-2 and IL-12 induced CD69 expression and reduce production of IFNγ (122).…”
Section: Msc As a Therapy In Post-transplant Carementioning
confidence: 99%